(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and paraclinical features and evaluate the treatment outcomes of post-neurosurgical meningitis and ventriculitis. Subjects and methods: A prospective descriptive study was conducted on 146 patients who underwent cranial surgery treated in the Surgical Intensive Care Unit. Results: Among the 146 patients who underwent cranial surgery, 36 developed meningitis and ventriculitis representing an incidence rate of 24.7%. The most common clinical manifestations were fever (100%) and altered consciousness (50%). All patients had cerebrospinal fluid abnormalities including a median white blood cell count of 1.51 G/l (IQR, 0.002-22.42), a median protein concentration of 1.92 g/l (IQR, 0.45-1.91), a mean glucose level of 2.89 ± 1.64 mmol/l, and a mean lactat concentration of 5.19 ± 2.25 mmol/l. The mean peripheral blood leukocyte count was 14.85 ± 3.97 G/L, the median serum procalcitonin level was 2.27 ng/ml (IQR, 0.15-56.58), and the mean serum C-reactive protein level was 103.15 ± 55.04 mg/l. Microbiological etiology was identified in 4 patients (11.1%), predominantly involving Gram-negative bacteria. Overall treatment outcomes showed that 9 patients (25%) died. The average duration of treatment in the intensive care unit was 19.42 ± 8.93 days. Conclusion: The most common clinical manifestations of meningitis and ventriculitis are fever and impaired consciousness. Cerebrospinal fluid analysis demonstrates abnormalities including elevated white cell count and protein levels, decreased glucose concentration, notably, increased lactat levels in all cases. However, the rate of positive cerebrospinal fluid cultures remains low, highlighting the diagnostic limitations of this method and underscoring the importance of combining clinical evaluation with biochemical analysis.